The unified parkinson's disease rating scale score in parkinson's disease patients with and without cognitive impairment - Hilmi, Abdullah (2007)
Parkinson's disease (PD) is widely known as a 'motor' disease, but it also has several non-motor features including cognitive impairment. Cognitive impairment has significant impacts on several aspects of PD. There is as yet a study on cognitive impairment and PD done involving our population. Objectives: To compare the Unified Parkinson's Disease Rating Scale (UPDRS) score between PD patients with and without cognitive impairment. Secondly, to determine the prevalence of cognitive impairment in patients with PD under Hospital Universiti Sains Malaysia (HUSM) follow-up. Methods: This was a cross-sectional study done at the HUSM Neurology Clinic, beginning from June till November 2006. Eighty PD patients who satisfied the study criteria were recruited into the study. Their cognitive status was assessed using the validated Malay version of the Mini-Mental State Examination (MMSE). A score of :S 24/30 signified presence of cognitive impairment while> 24/30 was normal. Regardless of their MMSE scores, all the patients then underwent assessment using the UPDRS. The UPDRS contains four items i.e. mentation, behaviour, and mood; activities of daily living; motor examination; and complications of therapy. Scores were taken from each item, and they were then totaled to obtain a total score. The study protocol was reviewed and approved by the USM Ethics and Research Committee. Results: Thirty two patients (40%) had cognitive impairment, ranging from mild to severe, based on the MMSE. Patients with cognitive impairment had significantly worse